2021
DOI: 10.1038/s41467-021-22743-7
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic functional neuron-type selectivity of transcranial focused ultrasound neuromodulation

Abstract: Transcranial focused ultrasound (tFUS) is a promising neuromodulation technique, but its mechanisms remain unclear. We hypothesize that if tFUS parameters exhibit distinct modulation effects in different neuron populations, then the mechanism can be understood through identifying unique features in these neuron populations. In this work, we investigate the effect of tFUS stimulation on different functional neuron types in in vivo anesthetized rodent brains. Single neuron recordings were separated into regular-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
114
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 97 publications
9
114
1
1
Order By: Relevance
“…The relative expression of these channels in different neuronal subtypes may also impact the extent to which various populations of neurons in the brain respond to ultrasound. Indeed, recent studies are starting to examine the contributions of various cell types to the brain’s response to FUS using intracranial electrical recordings 28 , 34 , 35 , 71 . These studies could be extended in the future by performing in vivo knockdowns of specific ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…The relative expression of these channels in different neuronal subtypes may also impact the extent to which various populations of neurons in the brain respond to ultrasound. Indeed, recent studies are starting to examine the contributions of various cell types to the brain’s response to FUS using intracranial electrical recordings 28 , 34 , 35 , 71 . These studies could be extended in the future by performing in vivo knockdowns of specific ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yu et al. provided evidence that the excitatory RS neurons and inhibitory FS neurons had different responses to ultrasound and the specific neuron types could be preferentially targeted by tuning the pulse repetition frequency (PRF) of ultrasound pulse in in vivo anesthetized rodent brains ( Yu et al., 2021 ). However, the precise mechanism of the rTUS modulation on the M1 region and its network effect requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate ramping reduced the unpleasantness and intrusiveness of the TUS 'sound', "turning it from a jackhammer to birdsong" in the words of one participant. Reducing intensity is likely an alternative method for preventing perception, but so far limited studies have found neuronal effects in this power range [10]. While this is by no means an exhaustive study of all TUS parameters, these results should motivate researchers to assess audibility of their own protocols, take measures to improve blinding and control experimentally for auditory confounds, guaranteeing that any measured brain or behavioural effects are due to direct neural modulation by TUS.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%